Magnesium alloy material for shielding high-energy particles and method for manufacturing the same

CN117965986BActive Publication Date: 2026-10-27CHONGQING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311689936.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2026-10-27
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

[0007]针对现有技术中所存在的不足,本发明提供了一种屏蔽高能粒子的镁合金材料及其制备方法,其解决了现有技术中镁合金材料屏蔽高能粒子的性能不够优异的问题

Benefits of technology

[0019]1、本发明制备的屏蔽高能粒子的镁合金材料通过添加Gd元素同时提高屏蔽高能粒子的性能和强度,Pb元素则能够吸收二次射线(即γ射线),添加Zr元素进一步提高镁合金材料的强度和塑性,最终获得一种具备良好综合性能的镁合金材料,可广泛应用于具有轻量化需求条件的屏蔽工况。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The magnesium alloy material for shielding high-energy particles comprises the following components in percentage of mass: Gd: 5-20.0%; Pb: 2-20.0%; Zr: 0.10-0.30%, and the rest is Mg and inevitable impurities; the application further provides a preparation method of the magnesium alloy material for shielding high-energy particles, characterized by comprising the following steps: (1) weighing the components of raw materials, melting Mg at 720-740 DEG C under inert protective atmosphere, adding the rest of the preheated components of raw materials after melting, and obtaining magnesium alloy ingot after complete melting, slag removal, casting and cooling; (2) performing plastic processing of the magnesium alloy ingot by extrusion or rolling; the application can improve the performance and strength of the magnesium alloy material for shielding high-energy particles by adding Gd element, Pb element can absorb gamma rays, and Zr element can further improve the strength and plasticity of the magnesium alloy material, so that a magnesium alloy material with good comprehensive performance is finally obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnesium alloy materials technology, specifically to a magnesium alloy material for shielding high-energy particles and its preparation method. Background Technology

[0002] With the widespread application of nuclear energy, nuclear radiation shielding is receiving increasing attention. Fast neutrons, thermal neutrons, and gamma rays generated during the operation of nuclear reactors have extremely strong penetrating power, which can not only seriously damage the health of personnel, but also seriously affect the normal operation of equipment and systems.

[0003] Therefore, how to efficiently shield neutrons and gamma rays is a crucial issue facing nuclear energy applications. Currently, commonly used shielding materials include: boron steel, which possesses neutron attenuation capabilities and excellent mechanical properties. However, boron has extremely low solubility in steel, and the presence of trace amounts (0.001%–0.007%) of boron increases the hardenability of the steel; excessively high boron content also negatively impacts the ductility and impact resistance of boron steel. Therefore, although boron steel has become one of the commonly used shielding materials in radiation protection design, it is mostly used for control rods and spent fuel storage materials. Lead-boron polyethylene has slightly insufficient structural properties, with slightly poor high-temperature resistance, radiation resistance, and corrosion resistance, and can only be used as a single-function material. Concrete offers high compositional flexibility, is inexpensive, can be sourced locally, and provides good shielding against radiation of various energy levels. However, ordinary concrete has a density of 2.2–2.4 g / cm³ and relatively low strength. To improve the mechanical strength and neutron and gamma-ray shielding performance of concrete, methods such as doping with mineral admixtures or natural / artificial functional coarse and fine aggregates are often used to prepare high-performance concrete or heavy concrete. Although the performance in various aspects is improved, it is bulky and heavy (density 3.0–6.0 g / cm3). Other metal-based materials, such as tungsten, have a good moderating effect on fast neutrons; fast neutrons can be shielded by 93% when passing through a 10 cm thick tungsten plate, but tungsten is expensive. However, by adding nickel, copper, cobalt, molybdenum, and chromium to tungsten to create alloys (70%–99% tungsten by mass), the density reaches as high as 16.5–19.0 ​​g / cm3, and these are called high-density alloys. These materials have advantages such as high specific gravity, high strength, strong radiation absorption capacity, high thermal conductivity, good weldability, and good machinability. Hafnium, samarium, cadmium, and other metals have also been used to prepare neutron and gamma-ray shielding materials, but due to their scarcity, high price, large secondary radiation output, and toxicity, they are rarely used in practice or are gradually being replaced by other materials.

[0004] Currently, although traditional materials such as water, lead, and concrete are still widely used in the field of reactor radiation protection, they still have obvious shortcomings. They are mostly used in stationary nuclear power reactors and accelerators, where price is the primary factor, and there are generally no strict requirements on the weight and volume of shielding materials.

[0005] To address the aforementioned issues, Chinese invention patent CN111968769B discloses a high-temperature resistant fast neutron shielding material, a composite shielding material, and a method for preparing the same. The fast neutron shielding material is composed of zirconium hydride, magnesium, and / or magnesium alloys; while the composite shielding material is a composition of zirconium hydride, magnesium, and / or magnesium alloys, elemental boron, and / or boron carbide and / or tungsten. However, elemental boron is difficult to dissolve in magnesium, making it difficult to obtain boron-containing magnesium alloy materials. Furthermore, the transmutation product of boron after neutron absorption is B... 11 The neutron absorption cross section of boron decreases sharply, and the neutron absorption effect becomes extremely poor, making it difficult for boron-containing materials to serve for a long time in a high-dose neutron environment. Therefore, new materials that are resistant to high temperatures, have excellent mechanical properties, are environmentally friendly and non-toxic, and whose shielding performance can be improved by adding neutron-absorbing elements have become a research hotspot and challenge.

[0006] Magnesium and zirconium have very small neutron capture cross-sections and are generally used in reactors. Magnesium alloys were first used in some gas-cooled reactors, while zirconium alloys have always been the cladding material for pressurized water reactor fuel. Rare earth element gadolinium has an excellent neutron capture cross-section and can effectively absorb neutrons. Furthermore, the transmutation products of gadolinium are shown below: Its transmutation products also possess a very large trapping cross section, making it an excellent neutron absorber material. Zirconium exhibits excellent grain refinement effects. Zirconium produces gamma rays after absorbing neutrons, while lead has the characteristic of absorbing gamma rays. Based on these reasons, this invention uses gadolinium's neutron absorption characteristics as the neutron absorber, lead as the gamma ray absorber, and zirconium as the grain refiner to develop a Mg-Gd-Pb-Zr alloy with excellent neutron shielding capabilities, which can be widely used in shielding applications requiring lightweight materials. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a magnesium alloy material for shielding high-energy particles and its preparation method, which solves the problem that the performance of existing magnesium alloy materials in shielding high-energy particles is not good enough.

[0008] A magnesium alloy material for shielding high-energy particles comprises, by mass percentage: Gd: 5-20.0%; Pb: 2-20.0%; Zr: 0.10-0.30%, with the remainder being Mg and unavoidable impurities.

[0009] This invention also provides a method for preparing a magnesium alloy material that shields high-energy particles, characterized by comprising the following steps:

[0010] (1) Weigh each raw material component and melt Mg at 720-740℃ under an inert protective atmosphere. After melting, add the remaining preheated raw material components. After complete melting, remove slag, cast and cool to obtain magnesium alloy ingot.

[0011] (2) Extrusion or rolling plastic processing is performed on the cooled magnesium alloy ingot.

[0012] Preferably, in step (1), after each raw material component is completely melted, it needs to be stirred first, and then the floating residue is removed.

[0013] Preferably, in step (1), the molten liquid of each raw material component needs to be allowed to stand for 15-20 minutes before casting.

[0014] Preferably, the inert protective atmosphere is a mixture of CO2 and SF6, wherein the volume ratio of CO2 to SF6 in the mixture is 99:1.

[0015] Preferably, a covering agent is used for protection in step (1).

[0016] Preferably, before plastic processing in step (2), the cooled magnesium alloy ingot needs to be solution treated at a temperature of 400-500℃.

[0017] Preferably, the purity of Mg in the raw material components is above 99.99%, the purity of Pb is above 99%, Gd is added in the form of 10.0%-30.0% Mg-Gd master alloy, and Zr is added in the form of 10.0%-30.0% Mg-Zr master alloy, and the purity of both Mg-Gd master alloy and Mg-Zr master alloy is above 99.9%.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The magnesium alloy material for shielding high-energy particles prepared by this invention improves the performance and strength of shielding high-energy particles by adding Gd element, while Pb element can absorb secondary rays (i.e. gamma rays), and Zr element further improves the strength and plasticity of magnesium alloy material. Finally, a magnesium alloy material with good comprehensive performance is obtained, which can be widely used in shielding conditions with lightweight requirements.

[0020] 2. The magnesium alloy material for shielding high-energy particles prepared by this invention has good shielding performance, with neutron energies between 0.018 eV and 0.25 eV, and a shielding coefficient of over 0.99. Moreover, the magnesium alloy material for shielding high-energy particles prepared by this invention also has the advantages of high temperature resistance, good mechanical properties, and being environmentally friendly and non-toxic.

[0021] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation

[0022] To make the technical means, creative features, objectives, and effects of this invention clearer and easier to understand, the invention will be further described below in conjunction with specific embodiments:

[0023] Example 1

[0024] The preparation process of Mg-Gd-Pb-Zr magnesium alloy is as follows:

[0025] 1) Using Mg ingots with a purity of 99.99%, Pb ingots with a purity of 99.9%, Mg-Gd master alloy with a purity of 99.9%, and Mg-Zr master alloy as raw materials, wherein the mass percentage of Gd in the Mg-Gd master alloy is 10%, and the mass percentage of Zr in the Mg-Zr master alloy is 10%; according to the composition, Gd 5%, Pb 2%, Zr 0.1%, and the remainder is Mg are weighed by mass percentage.

[0026] 2) Under a protective atmosphere of a mixed gas of CO2 and SF6 at a volume ratio of 99:1, Mg was first melted at 720℃. After the Mg melted, Pb, preheated Mg-Gd master alloy, and Mg-Zr master alloy were added. After all the solid metals had melted, the mixture was stirred to ensure uniform distribution of the alloying elements in the crucible. The floating residue was removed, and after standing for 15 minutes, the mixture was cast in a tantalum crucible preheated to 210℃ to obtain the as-cast alloy. After the ingot cooled, a magnesium alloy ingot was obtained. The magnesium alloy ingot was then solution treated at 400℃, followed by plastic processing to obtain the magnesium alloy product.

[0027] 3) The magnesium alloy products obtained after testing have a shielding coefficient of 0.99 or higher when the neutron energy is below 0.056 eV.

[0028] Example 2

[0029] The preparation process of Mg-Gd-Pb-Zr magnesium alloy is as follows:

[0030] 1) Using Mg ingots with a purity of 99.99%, Pb ingots with a purity of 99.9%, Mg-Gd master alloy with a purity of 99.9%, and Mg-Zr master alloy as raw materials, wherein the mass percentage of Gd in the Mg-Gd master alloy is 25%, and the mass percentage of Zr in the Mg-Zr master alloy is 25%; according to the composition, Gd 10%, Pb 6%, Zr 0.2%, and the remainder is Mg are weighed by mass percentage.

[0031] 2) Under a protective atmosphere of a mixed gas of CO2 and SF6 at a volume ratio of 99:1, Mg was first melted at 730℃. After the Mg melted, Pb, preheated Mg-Gd master alloy, and Mg-Zr master alloy were added. After all the solid metals had melted, the mixture was stirred to ensure uniform distribution of the alloying elements in the crucible. The floating residue was removed, and after standing for 16 minutes, the mixture was cast in a tantalum crucible preheated to 210℃ to obtain the as-cast alloy. After the ingot cooled, a magnesium alloy ingot was obtained. The magnesium alloy ingot was then solution-treated at 400℃, and subsequently plastically processed to obtain the magnesium alloy product.

[0032] 3) The magnesium alloy products obtained after testing have a shielding coefficient of 0.99 or higher when the neutron energy is below 0.075 eV.

[0033] Example 3

[0034] The preparation process of Mg-Gd-Pb-Zr magnesium alloy is as follows:

[0035] 1) Using Mg ingots with a purity of 99.99%, Pb ingots with a purity of 99.9%, Mg-Gd master alloy with a purity of 99.9%, and Mg-Zr master alloy as raw materials, wherein the mass percentage of Gd in the Mg-Gd master alloy is 25%, and the mass percentage of Zr in the Mg-Zr master alloy is 20%; according to the composition, Gd 15%, Pb 3%, Zr 0.3%, and the remainder is Mg are weighed by mass percentage.

[0036] 2) Under a protective atmosphere of a mixed gas of CO2 and SF6 at a volume ratio of 99:1, Mg was first melted at 720℃. After the Mg melted, Pb, preheated Mg-Gd master alloy, and Mg-Zr master alloy were added. After all the solid metals had melted, the mixture was stirred to ensure uniform distribution of the alloying elements in the crucible. The floating residue was removed, and after standing for 17 minutes, the mixture was cast in a tantalum crucible preheated to 210℃ to obtain the as-cast alloy. After the ingot cooled, a magnesium alloy ingot was obtained. The magnesium alloy ingot was then solution treated at 450℃, followed by plastic processing to obtain the magnesium alloy product.

[0037] 3) The magnesium alloy products obtained by testing have a shielding coefficient of 0.99 or higher when the neutron energy is below 0.093 eV.

[0038] Example 4

[0039] The preparation process of Mg-Gd-Pb-Zr magnesium alloy is as follows:

[0040] 1) Using Mg ingots with a purity of 99.99%, Pb ingots with a purity of 99.9%, Mg-Gd master alloy with a purity of 99.9%, and Mg-Zr master alloy as raw materials, wherein the mass percentage of Gd in the Mg-Gd master alloy is 20%, and the mass percentage of Zr in the Mg-Zr master alloy is 25%; according to the composition, Gd 20%, Pb 10%, Zr 0.3%, and the remainder is Mg are weighed by mass percentage.

[0041] 2) Under a protective atmosphere of a mixed gas of CO2 and SF6 at a volume ratio of 99:1, Mg was first melted at 720℃. After the Mg melted, Pb, preheated Mg-Gd master alloy, and Mg-Zr master alloy were added. After all the solid metals had melted, the mixture was stirred to ensure uniform distribution of the alloying elements in the crucible. The floating residue was removed, and after standing for 18 minutes, the mixture was cast in a tantalum crucible preheated to 210℃ to obtain the as-cast alloy. After the ingot cooled, a magnesium alloy ingot was obtained. The magnesium alloy ingot was then solution-treated at 500℃, and subsequently plastically processed to obtain the magnesium alloy product.

[0042] 3) The magnesium alloy products obtained by testing have a shielding coefficient of 0.99 or higher when the neutron energy is below 0.093 eV.

[0043] Example 5

[0044] The preparation process of Mg-Gd-Pb-Zr magnesium alloy is as follows:

[0045] 1) Using Mg ingots with a purity of 99.99%, Pb ingots with a purity of 99.9%, Mg-Gd master alloy with a purity of 99.9%, and Mg-Zr master alloy as raw materials, wherein the mass percentage of Gd in the Mg-Gd master alloy is 30%, and the mass percentage of Zr in the Mg-Zr master alloy is 30%; according to the composition, 20% Gd, 20% Pb, 0.3% Zr, and the remainder is Mg are weighed by mass percentage.

[0046] 2) Under a protective atmosphere of a mixed gas of CO2 and SF6 at a volume ratio of 99:1, Mg was first melted at 740℃. After the Mg melted, Pb, preheated Mg-Gd master alloy, and Mg-Zr master alloy were added. After all the solid metals had melted, the mixture was stirred to ensure uniform distribution of the alloying elements in the crucible. The floating residue was removed, and after standing for 20 minutes, the mixture was cast in a tantalum crucible preheated to 210℃ to obtain the as-cast alloy. After the ingot cooled, a magnesium alloy ingot was obtained. The magnesium alloy ingot was then solution-treated at 500℃, and subsequently plastically processed to obtain the magnesium alloy product.

[0047] 3) The magnesium alloy products obtained by testing have a shielding coefficient of 0.99 or higher when the neutron energy is below 0.013 eV.

[0048] The shielding coefficient calculation method in the above embodiments is: K = (n o -n m ) / n o In the formula, K is the neutron shielding coefficient, and n o When testing unshielded material samples, the neutron flux received by the counting sphere, n m The neutron flux received by the counting sphere when the test sample is shielded by a material.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A magnesium alloy material for shielding high-energy particles, characterized in that, Calculated by mass percentage, it includes the following components: Gd: 5-20.0%; Pb: 2-20.0%; Zr: 0.10-0.30%, the remainder being Mg and unavoidable impurities.

2. The method for preparing a magnesium alloy material for shielding high-energy particles according to claim 1, characterized in that, Includes the following steps: (1) Weigh each raw material component, melt Mg at 720-740℃ under an inert protective atmosphere, add the remaining preheated raw material components after melting, and obtain magnesium alloy ingots after slag removal, casting and cooling after complete melting. (2) Extrusion or rolling plastic processing is performed on the cooled magnesium alloy ingot.

3. The method for preparing a magnesium alloy material for shielding high-energy particles according to claim 2, characterized in that, In step (1), after each raw material component is completely melted, it needs to be stirred first, and then the floating residue is removed.

4. The method for preparing a magnesium alloy material for shielding high-energy particles according to claim 2, characterized in that, In step (1), the molten liquid of each raw material component needs to be allowed to stand for 15-20 minutes before casting.

5. The method for preparing a magnesium alloy material for shielding high-energy particles according to claim 2, characterized in that, The inert protective atmosphere is a mixture of CO2 and SF6, with a volume ratio of CO2 to SF6 of 99:

1.

6. The method for preparing a magnesium alloy material for shielding high-energy particles according to claim 2, characterized in that, In step (1), a covering agent is used for protection.

7. The method for preparing a magnesium alloy material for shielding high-energy particles according to claim 2, characterized in that, Before plastic processing in step (2), the cooled magnesium alloy ingot needs to be solution treated at a temperature of 400-500℃.

8. A method for preparing a magnesium alloy material for shielding high-energy particles according to any one of claims 2-7, characterized in that, The raw material components contain Mg with a purity of ≥99.99%, Pb with a purity of ≥99%, Gd added in the form of 10.0%-30.0% Mg-Gd master alloy, and Zr added in the form of 10.0%-30.0% Mg-Zr master alloy, with the purity of both the Mg-Gd master alloy and the Mg-Zr master alloy being ≥99.9%.

Citation Information

Patent Citations

  • A high-temperature resistant fast neutron shielding material, a composite shielding material and its preparation method

    CN111968769B

  • Magnesium-based materials with combined X-ray and neutron shielding effects

    CN102260812A